2015
DOI: 10.1080/13645579.2015.1062628
|View full text |Cite
|
Sign up to set email alerts
|

Using video and dialogue to generate pedagogic knowledge: teachers, learners and researchers reflecting together on the pedagogy of social research methods

Abstract: Developments in pedagogical knowledge in the teaching of social research methods have largely been generated through teachers reflecting on their practice. This paper presents an alternative approach to generating data through reflective dialogue between researchers, teachers and learners. The approach incorporates elements of video stimulated recall and reflective dialogue within focus group interviewing. The rationale and affordances are discussed in relation to the goals of discussing teachers' pedagogical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…In this sense, they demonstrate strong content knowledge (a knowledge of method), but, as Nind et al (2015b) observe, they do not necessarily have the pedagogic knowledge (including that specific to the subject matter, pedagogic content knowledge, (Shulman, 1986)) associated with excellent learning experiences. For the purposes of sharing pedagogic experience and insight, it was therefore necessary to recruit participants with both teaching and methodological expertise who could share their pedagogical content knowledge.…”
Section: Expertise In Methods and Pedagogymentioning
confidence: 99%
“…In this sense, they demonstrate strong content knowledge (a knowledge of method), but, as Nind et al (2015b) observe, they do not necessarily have the pedagogic knowledge (including that specific to the subject matter, pedagogic content knowledge, (Shulman, 1986)) associated with excellent learning experiences. For the purposes of sharing pedagogic experience and insight, it was therefore necessary to recruit participants with both teaching and methodological expertise who could share their pedagogical content knowledge.…”
Section: Expertise In Methods and Pedagogymentioning
confidence: 99%
“…We used video-stimulated recall, reflection and dialogue to draw out that which is hard to know in pedagogy: the ingrained, unconscious and implicit (Nind, Kilburn, and Wiles 2015). This involved focus groups of methods teachers and learners looking back together on video excerpts of a teaching event immediately afterwards.…”
Section: Methodsmentioning
confidence: 99%
“…TIMSS video study) teachers gain opportunities to learn about effective practices (Hatch & Grossman, 2009) and new instructional strategies (Sherin & Han, 2004). The effects of watching classroom videos are also demonstrated in relation to teachers' motivation, activation of prior knowledge (Lemke, 2007;Nind, Kilburn & Wiles, 2015) and noticing areas of their own teaching about which they were previously unaware (Tripp & Rich, 2012;Zhang, Lundeberg, Koehler & Eberhard, 2011). In particular, it has been shown that when teachers observe their own video-recorded teaching, they tend to activate contextualized knowledge 167 TEACHERS' PERCEPTIONS OF TEACHING AND LEARNING IN THE CLASSROOM SETTINGS about their classroom and their teaching (Borko et al, 2008;Seidel, Stürmer, Blomberg, Kobarg, & Schwindt, 2011).…”
Section: Theoretical Frameworkmentioning
confidence: 99%